2022
DOI: 10.3390/curroncol29010024
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon EGFR Compound Mutations in Non-Small Cell Lung Cancer (NSCLC): A Systematic Review of Available Evidence

Abstract: Compound epidermal growth factor receptor (EGFR) mutations represent a heterogeneous subgroup of non-small cell lung cancer (NSCLC) patients with uncommon EGFR mutations. We conducted a systematic review to investigate the available data on this patients’ subgroup. Overall, we found a high heterogeneity in the incidence of compound mutations (4–26% of total EGFR mutant cases), which is dependent on the different testing methods adopted and the specific mutations considered. In addition, the relative incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 52 publications
(69 reference statements)
4
32
1
Order By: Relevance
“…Uncommon EGFR mutations can occur alone or coexist with either common or other uncommon EGFR mutations, including complex or compound mutations. The incidence of complex EGFR mutations varies among different study populations and detection methods, ranging from 4% to 26% of all EGFR mutations ( 15 ). Data regarding the effect of EGFR -TKIs on complex EGFR mutations are even fewer, and the results based on a relatively small number of cases were highly heterogeneous ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uncommon EGFR mutations can occur alone or coexist with either common or other uncommon EGFR mutations, including complex or compound mutations. The incidence of complex EGFR mutations varies among different study populations and detection methods, ranging from 4% to 26% of all EGFR mutations ( 15 ). Data regarding the effect of EGFR -TKIs on complex EGFR mutations are even fewer, and the results based on a relatively small number of cases were highly heterogeneous ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of complex EGFR mutations varies among different study populations and detection methods, ranging from 4% to 26% of all EGFR mutations ( 15 ). Data regarding the effect of EGFR -TKIs on complex EGFR mutations are even fewer, and the results based on a relatively small number of cases were highly heterogeneous ( 15 ). Generally, the result in patients carrying complex mutations is similar to that in patients with single uncommon mutations and is less favorable than that in patients with common mutations ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound mutations indicate the presence of more than one EGFR mutation, either common or uncommon, within the same tumor. Attili et al ( 98 ) found high heterogeneity in the incidence of compound mutations (4–26% of total EGFR mutant cases), with the variance possibly due to the different testing methods adopted, and the specific mutations considered. In various combinations, compound EGFR mutations containing either exon 21 p. L858R or exon 19 deletions were common ( 99 ).…”
Section: Drug Resistance Mechanisms and Progress In The Use Of First-...mentioning
confidence: 99%
“…(Melosky et al, 2022). A classic or common EGFR alterations mainly comprise an in-frame deletion in exon 19 and L858R missense mutation in exon 21, accounting for about 80%-90% of EGFR alterations in NSCLC (Attili et al, 2022). Approximately 10% of patients with NSCLC harbor uncommon EGFR alterations including major uncommon mutation G719X, L861Q and S768I (Figure 1), de novo T790M mutation and exon 20 insertions, or their compound forms including the co-existence of common or uncommon mutation (Russo et al, 2019;Zhang et al, 2019;Gristina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%